The Influence Of Attributes And Brand Awareness On The Decision To Use Maxim Online Transportation Services In Gunungsitoli City - Ndraha, Oktaviani; Yuterlin Zalukhu; Harefa, Idarni; Zebua, Serniati (Universitas Dehasen Bengkulu, 2025)
The background of this study is that there are still drivers who do not use attributes such as jackets, helmets and stickers when driving or driving on the road. Where this does not maximize the existence of the Maxim brand to be known or known to the public and affects consumer comfort and consumer trust. This study aims to determine how much influence attributes and brand awareness have on the decision to use Maxim online transportation services in Gunungsitoli City. This study employed a quantitative approach with a survey method. Data were collected by distributing questionnaires to 98 respondents selected using random probability sampling. The data analysis method employed in this study included multiple linear regression techniques to evaluate the significant impact of the independent variables on the dependent variable and to identify relationships between the variables studied. The results of this study indicate that attributes, brand awareness have a positive and significant effect on usage decisions. With high attributes (service quality, product features, branding, labeling, applying style and design) and brand awareness (recall, recognition, purchase and consumption owned will be easier to increase the decision to use Maxim online transportation services in Gunungsitoli City.